2001
DOI: 10.1159/000030152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cyfra 21-1 and SCC Assays in Head and Neck Tumours

Abstract: Patients with head and neck tumours (HNT) have a high risk of early locoregional relapse that is difficult to diagnose. This study evaluated the usefulness of the serum Cyfra 21-1 assay compared to squamous cell carcinoma antigen (SCC) assay for monitoring such patients. Three hundred and twelve HNT patients, including 204 newly diagnosed patients, were followed up for a median of 446 days with serial serum assays for SCC and Cyfra 21-1. Untreated patients showed SCC and Cyfra 21-1 serum levels correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
2
27
1
2
Order By: Relevance
“…The data including our study have shown that CYFRA 21-1 is a good marker for monitoring therapeutic effect, follow-up and prognostic value in patients with HNSCC. [2][3][4][5] Furthermore, many studies have shown that CYFRA 21-1 is useful for diagnosis of HNSCC. [5][6][7][8][9][10] We also believe that CYFRA 21-1 is an adjunct for the diagnosis of HNSCC.…”
Section: Elecsys 2010 Cyfra 21-1 Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The data including our study have shown that CYFRA 21-1 is a good marker for monitoring therapeutic effect, follow-up and prognostic value in patients with HNSCC. [2][3][4][5] Furthermore, many studies have shown that CYFRA 21-1 is useful for diagnosis of HNSCC. [5][6][7][8][9][10] We also believe that CYFRA 21-1 is an adjunct for the diagnosis of HNSCC.…”
Section: Elecsys 2010 Cyfra 21-1 Assaymentioning
confidence: 99%
“…Also, a decrease of the Cyfra 21-1-serum concentration after therapy in patients with squamous cell carcinomas of the head and neck has been seen earlier. 4 Cyfra 21-1 is a well accepted tumour marker in non-small-cell lung cancer. 6 The controversy about the usefulness of Cyfra 21-1 as serum tumour marker in head and neck squamous cell carcinomas is probably due to dif culties to nd the appropriate cut-off level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Tumor Biology three papers by Nap et al [2], Miédougé et al [3], and Banal et al [4] deal specifically with these cytokeratins, and their value as tumor markers. Their findings will be discussed in the context of our existing knowledge of cytokeratin structure and function.…”
mentioning
confidence: 99%
“…In this issue two reports [3,4] are presented, indicating that cytokeratin 19 fragments (assayed by the Cyfra 21:1 assay) appear in extracellullar fluids during malignant diseases. These fragments are supposed to be generated by the proteolytic cleavage of cytokeratins in tumor cells, rendering the cytokeratins more soluble.…”
mentioning
confidence: 99%